The Strategic Role of Information Systems in Advancing Sustainable Business Practices - Puspitasari, Devi (Data : Journal of Information Systems and Management, 2024)
Information systems are increasingly recognized as enablers of sustainable business practices. However, the extent of their impact across environmental, social, and governance (ESG) dimensions remains limited in current scholarship, particularly regarding mechanisms of influence. This narrative review investigates how information systems contribute to sustainability by enhancing operational efficiency, informing strategic decisions, and overcoming implementation challenges. Drawing from Scopus and Google Scholar, a systematic search was conducted using Boolean keyword combinations such as "Information Systems" AND "Sustainable Business Practices" and "Digital Transformation" AND "Sustainable Development." Studies meeting inclusion criteria—focused on the integration of IT in sustainability efforts—were synthesized thematically. The findings indicate that information systems significantly improve energy efficiency, reduce waste, and support environmental accounting. They enable real-time monitoring, predictive analytics, and decision-making frameworks grounded in ESG principles. Big data and cloud platforms are shown to facilitate cross-functional collaboration and innovation. However, implementation is often hindered by infrastructural limitations, high costs, and resistance to change, especially in developing regions. The role of regulatory support and organizational culture emerged as critical systemic enablers. Comparative insights between countries highlighted best practices that can be adapted to local contexts. This review concludes that information systems are not merely tools but strategic assets for sustainability. Policy incentives, capacity-building, and inclusive digital infrastructure are recommended to bridge implementation gaps. Future research should explore the integration of emerging technologies for enhanced impact. Promoting awareness and access remains essential to scaling sustainable practices globally.